Поняття «торговельна марка» та ведення його обліку - Бегун, Світлана Іванівна; Берегович, Катерина Миколаївна; Begun, Svitlana I.; Berehovych, Kateryna M. (Луцький національний технічний університет, 2014)
У статті було досліджено сутність поняття «торговельна марка», законодавчий процес його реєстрації. Також розглянуто процес відображення обліку торговельної марки на підприємстві. In the article essence of concept «trade mark» and his varieties was investigational, actuality of the chosen theme, and also necessity a domain of the trade mark, is explained by an enterprise. Each is described of types of trade mark and examples are resulted to them. One with the major moment of domain a trade mark is a presence of certificate as a token of commodities and services. So the stage-by-stage legislative process of registration of trade mark was therefore considered, all necessary terms for its assertion, and also the term of domain a certificate is described. In the article the amount of the registered certificates of national and foreign trade marks were analysed on the legislation of Ukraine, and also comparing of change to the last year. The reflection of account of trade mark is considered on the accounts of recordkeeping on an enterprise. Elements are described from which the primitive cost of right of ownership is formed on a trade mark. The reflection of charges related to forming and exercising right is also described in a record-keeping. The features of charging amortization are considered on an immaterial asset. As, an enterprise can independently choose the term of the useful use of immaterial asset, that is why the factors of his influence are indicated in the article.
The concept of «trade mark» and doing his account
Keywords: торговельна марка; реєстрація; облік торговельної марки; trademark registration